MODEL PEMBELAJARAN PENDIDIKAN INKLUSIF UNTUK ANAK YANG MENGALAMI KESULITAN BELAJAR - AHDIYAT, MAMAN; AGUSTINA, LASIA; HIKMAH, NURUL (E-Jurnal Matematika, 2017)
The objective of this research is to obtain data about the model of learning that is designed specifically for children who have difficulty in studying in the State Elementary School of Inclusive Education in South Jakarta. The research is done by Research and Development method with qualitative approach with descriptive analysis Observation and documentary study). Population is State Elementary School Provider of Inclusive Education in South Jakarta with a large sample of 10 schools, with sampling technique used is random sampling. Instrument research used questionnaire. Result is: 1) There is no single school that uses a specific learning model for children with learning difficulties,  2) The learning model used still uses conventional learning model where children are treated the same as normal children (no learning difficulties).